Pengembangan Mesin Pengupas Kulit Buah Aren Dengan Metode Quality Function Deployment (Qfd) - Robert Napitupulu; Zaldy Sirwansyah Suzen (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
This study aims to determine whether the development of palm fruit peeler machine by using Quality Function Deployment (QFD) can optimize the results of the palm fruit peeling in Balun Ijuk village, Bangka. The method used in the data collection is to survey the place, interview and distribute the questionnaires to the respondents. While the analysis of the data is by using the descriptive methods. The data obtained is analyzed by using the QFD, while the design and the engine development is made based on the analysis and interpretation of the House of Quality (HOQ), which is the result of QFD. Furthermore, to determine whether the tool is made completely in accordance with the demand of the consumer, then the machine is made and the tests to determine the level of need and customer satisfaction. The result of the study shows that the machine is able to peel more and the result of the peeling is that the machine can separate the skin from the seed by using the motor of 1PK electric power. While from the consumen satisfaction, it can be concluded that the price is affordable, the machine is durable and not easily porous, the performance of the tool is fast, it is easy to be operated, it saves more space, and easy to replace the spare parts.